POSSIBLE ADVERSE EVENTS DURING IBD TREATMENT. - Adriana Krasteva; Assya Krasteva; Angelina Kisselova (Peytchinski Publishing, 2011)
Inflammatory bowel diseases (IBD) refer to two chronic diseases which involve the large and small intestines: ulcerative colitis and Crohn's disease.The aim of the review is to focus on main oral signs which are related to a specific treatment. Most of the articles on IBD patients consider just the typical oral disease manifestations, without taking into account oral manifestations as results from the administrated treatment.